MENINGKATKAN KETERAMPILAN MENULIS DENGAN PENGGUNAAN MEDIA SENI MURAL PADA PESERTA DIDIK KELAS VI SDN JAMBEARUM 02 SUMBERJAMBE TAHUN PELAJARAN 2020/2021: SDN JAMBEARUM 02 SUMBERJAMBE - ABDULLAH ABDULLAH (Mitra Pendidikan, 2021)
Writing skill is an important language aspect which students need to learn and master them. Writing skills can be realized in writing literary works in the essays. Writing is an effective communication activity to express ideas or ideas in writing attend to the words, shapes, properly and so on. Grade VI students at SDN Jambearum 02 faced same writing problems. Writing students activities were very difficult to increase because students have difficulty getting ideas, students lazy to write, especially essay when they have writing assignments by teacher. This research uses the type of classroom action research (CAR) or also called classroom action research. This CAR consists four stages, namely planning, action, observation, and reflection. This research was conducted at SDN Jambearum 02 . The subjects of the study were Grade VI SDN Jambearum 02 students , a total of 24 students. Meanwhile, research object is the writing skills of the sixth grade students of SDN Jambearum 02 in this classroom action research. This action research was carried out in two cycles. Each cycle was carried out in 2 meetings. There were increase in the content aspects from first cycle to second cycle of 0.71. Organizational aspect there is an increase of 0.18. The increase in the vocabulary aspect is 0.36. An increase in the language use aspect is 0.25. The increase in the Mechanical aspect is 0.3. Overall, from first cycle to second cycle the writing aspect increase was 1.89. In this study, the researchers focused on (1) the students ability in writing description before using Mural Art media (2) increasing students' writing skills using Mural Art media, and (3) improving the writing skills of Class VI students. SDN Jambearum 02 using Mural Art media.